Comparative analysis of radon concentrations in buildings of different energy efficiency classes on example of five Russian cities - I. V. Yarmoshenko; A. D. Onishchenko; G. P. Malinovsky; A. V. Vasilyev; E. I. Nazarov; M. V. Zhukovsky (Радиационная гигиена)
A comparative analysis of the radon concentrations in modern multi-storey residential buildings of high energy efficiency class and buildings typical for urban areas of the twentieth century was carried out. The study was conducted in Russian cities located in various climatic zones – Ekaterinburg, Krasnodar, St. Petersburg, Salekhard, Chelyabinsk. The radon concentration in samples of buildings was measured using integrated radon radiometers based on nuclear track detectors according to a single method. The surveyed sample included 498 apartments in multi-apartment buildings. Among all the examined building types, the highest average radon concentration is observed in modern energy-efficient houses – 43 Bq/m3. In other types of buildings, the following average radon concentrations were obtained: brick 2–5 floors – 35 Bq/m3; panel 5 floors – 32 Bq/m3; panel 7–12 floors 1970-1990 years of construction – 22 Bq/m3; brick> 5 floors 1970–1980 years of construction – 20 Bq m3; panel, built since 1990 – 24 Bq/m3. The results of the study confirm the assumption that radon concentration in modern multi-storey energy-efficient houses is on average higher than in typical residential buildings of the Soviet period. The increased accumulation of radon in energy-efficient buildings is associated with a decrease in the building envelope permeability and the contribution of fresh air to the general air exchange. Despite the fact that there were no cases of exceeding hygienic standards for the indoor radon concentration in the framework of this study, the higher radon concentration in buildings of increased energy efficiency requires attention from the point of view of implementing the principle of optimization of radiation protection. In the future, extensive construction of energy-efficient buildings may increase the average and collective doses to the urban population in the Russian Federation.